(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of laparoscopic colorectal resection with natural orifice specimen extraction (NOSE) in the treatment of colorectal cancer at Nghe An Oncology Hospital. Methods: A retrospective descriptive study was conducted on 38 patients with colorectal cancer who underwent laparoscopic colorectal resection with natural orifice specimen extraction at Nghe An Oncology Hospital from January 2023 to October 2025. Data on tumor characteristics, surgical features, and intraoperative and postoperative outcomes were collected from medical records and analyzed using SPSS 26.0. Results: The mean age was 56.4 ± 10.9 years, with a male-to-female ratio of 2.2/1. Tumors were most commonly located in the upper rectum (50%). Most patients were at T3 stage (71%) and had lymph node metastasis (73.7%). Anterior resection was performed in 65.8% of cases, and low anterior resection in 34.2%. Specimens were mainly extracted transanally (71.1%). The mean operative time was 139 ± 22 minutes. No intraoperative mortality, anastomotic leakage, or intra-abdominal abscess was recorded. Postoperatively, the mean pain score on postoperative day 2 was 3.2 ± 1.2. The mean time to flatus was 2.0 ± 0.8 days, time to oral intake was 1.5 ± 0.4 days, and length of hospital stay was 7.1 ± 0.7 days. Conclusion: Laparoscopic colorectal resection with natural orifice specimen extraction is a feasible and safe technique with favorable short-term outcomes in the treatment of colorectal cancer at Nghe An Oncology Hospital.